2004
DOI: 10.1136/bjsm.2002.003947
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three preventive methods in order to reduce the incidence of ankle inversion sprains among female volleyball players

Abstract: Background: Ankle sprains are the most common form of acute injury in volleyball. A prevention programme consisting of technical training, proprioceptive training, and external support was previously designed to reduce the rate of ankle sprains in volleyball players. Objective: To investigate which of these three interventions is the most effective in preventing ankle sprain in female volleyball players. Methods: Participants were 52 players who suffered ankle sprains during the season 1998-1999. They were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 20 publications
1
78
0
7
Order By: Relevance
“…7 As the ankle reinjury rate is known to be high, it is important to identify specific injury prevention strategies. 1,24 Measures to prevent injury have typically included specific strength training of the fibularis muscles, 26 proprioceptive training, 26,39 and external support, such as braces and nonelastic athletic tape. 2,12,26,39 Tests of postural control have shown that individuals with ankle instability have poorer frontal plane stability than those with unaffected ankles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 As the ankle reinjury rate is known to be high, it is important to identify specific injury prevention strategies. 1,24 Measures to prevent injury have typically included specific strength training of the fibularis muscles, 26 proprioceptive training, 26,39 and external support, such as braces and nonelastic athletic tape. 2,12,26,39 Tests of postural control have shown that individuals with ankle instability have poorer frontal plane stability than those with unaffected ankles.…”
mentioning
confidence: 99%
“…1,24 Measures to prevent injury have typically included specific strength training of the fibularis muscles, 26 proprioceptive training, 26,39 and external support, such as braces and nonelastic athletic tape. 2,12,26,39 Tests of postural control have shown that individuals with ankle instability have poorer frontal plane stability than those with unaffected ankles. 32 Due to their role as the primary everters and dynamic stabilizers of the ankle, the function of the fibularis (peroneus) muscles in relation to ankle stability and lateral sprains has been extensively studied.…”
mentioning
confidence: 99%
“…Prophylactic proprioception training was shown to reduce injuries in a prospective randomized study of 900 high school basketball players [100]. In patients with frequent ankle sprains, proprioception training was associated with a decreased risk of recurrent ankle instability when compared to use of an orthosis [101]. Prophylactic bracing may be useful as was shown in a prospective study of female volleyball players [102].…”
Section: Preventionmentioning
confidence: 96%
“…Several authors (Clark & Burden, 2005;Emery, Cassidy, Klassen, Rosychuk, & Rowe, 2005;Mcguine & Keene, 2006;Michell, Ross, Blackburn, Hirth, & Guskiewicz, 2006;Mohammadi, 2007;Sheth, Yu, Laskowki, & An, 1997;Stasinopoulos, 2004;Verhagen, Van Der Beek, Twisk, Bouter, Bahr, & Van Mechelen, 2004) have used ankle dish training as an effective form of treatment to reduce proprioception deficits, decrease peroneal latency time and increase postural control. Ankle disk training has been shown to significantly reduce the recurrence of ankle sprains (Verhagen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, more studies need to be conducted on healthy subjects (Stasinopoulos, 2004), and additional preventive strategies need to be developed in order to reduce the impact and cost of rehabilitation (Mckay et al, 2001), since proprioception training can be used to prevent the initial injury (Diamond, 1989).…”
Section: Introductionmentioning
confidence: 99%